Comparative demography of three neotropical larval-prepupal parasitoid species associated with Anastrepha fraterculus (Diptera: Tephritidae) - Núñez Campero, Segundo Ricardo (2014)
The South American fruit fly, Anastrepha fraterculus (Wiedemann), is one of two fruit fly species of economic importance in Argentina, which along with the exotic Mediterranean fruit fly, Ceratitis capitata (Wiedemann) produce annual losses of nearly US$ 90 million for fruit production in this country. Biological control may contribute to integrated approaches to manage both pestiferous species. Information on survival, reproduction and population growth parameters, critical for successful augmentation of natural enemies, is provided for three fruit fly neotropical parasitoids, Aganaspis pelleranoi (Hymenoptera: Figitidae), Opius bellus and Doryctobracon crawfordi (Hymenoptera: Braconidae). A. pelleranoi had the highest intrinsic reproductive rate (r), survival time and reproductive time, followed by O. bellus. Meanwhile D. crawfordi showed the lowest values for reproductive and population growth parameters.